Sensory gating in the hippocampus and the medial prefrontal cortex - Dissanayake, Watuthanthrige Dilshani Nadira (2008)
Sensory gating is a mechanism by which irrelevant sensory information is filtered in the brain, enabling efficient information processing. The auditory conditioning-test paradigm, an index of sensory gating, measures the reduction in the auditory-evoked response (AER) produced by a test stimulus following an initial conditioning stimulus. Schizophrenic patients demonstrate a lack of attenuation of the test response measured in the P50 component of the cortical auditory-evoked potential. The N2/N40 auditory-evoked potential recorded from rat hippocampus is considered homologous to the human P50 wave. Altered glutamatergic neurotransmission and the endocannabinoid system have been implicated in the pathogenesis of schizophrenia with structural and functional abnormalities in the hippocampus and the medial prefrontal cortex (mPFC).